T cell clonal expansions in ileal Crohn's disease are associated with smoking behaviour and postoperative recurrence. Issue 11 (12th February 2019) - Allez, Matthieu; Auzolle, Claire; Ngollo, Marjolaine; Bottois, Hugo; Chardiny, Victor; Corraliza, Ana Maria; Salas, Azucena; Perez, Kevin; Stefanescu, Carmen; Nancey, Stéphane; Buisson, Anthony; Pariente, Benjamin; et al.
Abstract : T cell clonal expansions are present in the inflamed mucosa of patients with Crohn's disease (CD) and may be implicated in postoperative recurrence after ileocolonic resection. Methods: T cell receptor (TCR) analysis was performed in 57 patients included in a prospective multicentre cohort. Endoscopic recurrence was defined by a Rutgeerts score >i0. DNA and mRNA were extracted from biopsies collected from the surgical specimen and endoscopy, and analysed by high throughput sequencing and microarray, respectively. Results: TCR repertoire in the mucosa of patients with CD displayed diverse clonal expansions. Active smokers at time of surgery had a significantly increased proportion of clonal expansions as compared with non-smokers (25.9%vs17.9%, p=0.02). The percentage of high frequency clones in the surgical specimen was significantly higher in patients with recurrence and correlated with postoperative endoscopic recurrence (area under the curve (AUC) 0.69, 95% CI 0.54 to 0.83). All patients with clonality above 26.8% (18/57) had an endoscopic recurrence. These patients with a high clonality were more frequently smokers than patients with a low clonality (61% vs 23%, p=0.005). The persistence of a similar TCR repertoire at postoperative endoscopy was associated with smoking and disease recurrence. Patients with high clonality showed increased expression of genes associated with CD8 T cells and reduced expression of inflammation-related genes. Expanded clones were found predominantly in the CD8 T cell compartment. Conclusion: Clonal T cell expansions are implicated in postoperative endoscopic recurrence. CD patients with increased proportion of clonal T cell expansions in the ileal mucosa represent a subgroup associated with smoking and where pathogenesis appears as T cell driven. Trial registration number: NCT03458195.